Data Mining and Its Applications for Knowledge Management: A Literature Review - R. A. Nikam, Ramesh Lavhe, Sayali Kokane, Ashok Kalal (Mathematical Statistician and Engineering Applications, 2019)
Data mining is a prominent area of knowledge management and is one of the most critical phases in the process of knowledge discovery in databases. It is also one of the most crucial steps in the process. In the future decades, research in data mining will continue to expand in both the commercial world and the world of learning organizations. The purpose of this review article is to investigate the uses of data mining methods that have been developed to help the process of knowledge management. After that, the logic behind knowledge management and the primary knowledge management instruments that are included into the knowledge management cycle are outlined. In conclusion, a discussion and summary of the many uses of data mining methods throughout the process of knowledge management are presented.